Residency of rhenium and osmium in a heavy crude oil - DiMarzio, Jenna, author; Stein, Holly, advisor; Hannah, Judith, advisor; Georgiev, Svetoslav, committee member; Finke, Richard, committee member (Colorado State University. Libraries, 2017)
The Re-Os geochronometer is an emerging tool for the study of oil formation and migration processes, and a new technology for petroleum exploration. Very little is known, however, about the residency of Re and Os within asphaltene and maltene sub-fractions of crude oil. This information is crucial for better understanding of petroleum systems in general, and especially for successful geochronology of key processes such as oil formation, migration, or biodegradation. In this work, a heavy crude oil was separated into soluble (maltene) and insoluble (asphaltene) fractions using n-heptane as the asphaltene-precipitating agent. The asphaltenes were separated sequentially into sub-fractions using two different solvent pairs (heptane-DCM and acetone-toluene), and the bulk maltene was separated into saturate, aromatic, and resin (SAR) fractions using open column chromatography. Each asphaltene and maltene sub-fraction was analyzed for Re and Os. The asphaltene sub-fractions and bulk samples were analyzed for a suite of trace metals by ICP-MS. Our results show that Re and Os concentrations co-vary between the asphaltene sub-fractions, and that both elements are found mostly in the highly polar, highly aromatic sub-fractions; significant Re and Os are also present in the aromatic and resin fractions of the maltenes. However, each asphaltene and maltene sub-fraction has a distinct isotopic composition, and these sub-fractions are not isochronous. This may suggest that asphaltene sub-fractionation separates Re-Os complexes to the point that the isotopic integrity of the geochronometer is undercut. The decoupling possibilities of radiogenically produced 187Os from Re remain elusive, and more work is needed to determine the mobility of radiogenically produced 187Os. Re-Os and Ni-V budgets track each other, suggesting that some Re and Os may form metalloporphyrins. On the other hand, Re correlates strongly with Mo and Cd in the asphaltene sub-fractions; as Re and Os track each other, this suggests that Re-Os, Mo, and Cd occupy similar sites. Finally, we suggest that progressive asphaltene precipitation during migration and mixing of oils can change the resultant oil's isotopic ratios. This is key to interpretation of Re-Os data for tar mats and live oils, whether the data form an isochron or scatter. By combining data from source rocks, oils, and asphaltenes generated along the migration pathway, we are constructing temporal histories for whole petroleum systems.